Development of a smart janitor assistant system - Lim, Ming Hui (Nanyang Technological University, 2022)
In recent years, scientists and the general public have become extremely worried about indoor air quality as people spend more than 70 percent of their time indoors. Furthermore, interior air pollution levels have been reported to be higher than outdoor levels in some investigations. Toilets are one of the contributing factors to poor air quality in indoor facilities that are frequently used by individuals, hence, there is a need to measure satisfactory air quality.